Kemampuan Menulis Paragraf Persuasif Siswa Kelas VIII SMP Negeri 6 Binjai - Yulinda Dwinata (Sintaks: Jurnal Bahasa & Sastra Indonesia, 2022)
This study aims to determine the ability to write persuasive paragraphs in class VIII SMP Negeri 6 Binjai. The research method used in this research is descriptive method. The research sample was carried out at random (random sampling) so that the sample was obtained, namely class VIII-1, which consisted of 40 students. Based on the data obtained, it can be seen that the Ability to Write Persuasive Paragraphs of Class VIII Students of SMP Negeri 6 Binjai with the average score obtained is 72. Thus, it can be seen that students of class VIII SMP Negeri 6 Binjai are quite capable of writing persuasive paragraphs, this can seen from the average value obtained by these students.